The Relationship Between Interpersonal Intelligence And Adolescents' Knowledge Of Bullying Prevention - Selvizinia Queisya Barros; Ni Made Nopita Wati; I Gede Juanamasta (Jurnal Medicare, 2026)
Bullying is a serious problem among adolescents that can negatively impact their mental health and social development. Interpersonal intelligence, which encompasses the ability to understand the feelings, intentions, and emotions of others, is believed to influence adolescents' knowledge of bullying and their ability to prevent it. This study aimed to determine the relationship between interpersonal intelligence and adolescents' knowledge of bullying prevention at Santa Angela Junior High School, Atambua. The study used a quantitative design with a descriptive correlational approach. The sample consisted of 122 students selected using probability sampling techniques. Data were collected through a questionnaire that measured interpersonal intelligence and knowledge of bullying. The results showed that the majority of respondents had high interpersonal intelligence (40.6%) and good knowledge of bullying (48.7%). Data analysis using the Spearman Rank correlation test showed a significant relationship between interpersonal intelligence and knowledge about bullying (r = 0.465; p = 0.000). Research indicates that interpersonal intelligence plays a crucial role in improving adolescents' knowledge about bullying, as they are better able to understand the social and emotional impacts of bullying behavior. Interpersonal intelligence is positively related to knowledge about bullying, which can aid in bullying prevention in schools. It is recommended that schools integrate the development of interpersonal intelligence into anti-bullying education programs to create a safer environment for students